The intangible : a novel - Washington, C. J. (Little A, 2022)
"Amanda Jackson has always longed to be a mother. The early weeks of her first pregnancy are a mixture of joy, anticipation, and uncertainty as she and her husband prepare for the journey ahead. Then comes a devastating loss. Even though her doctors tell her otherwise, Amanda believes she's still pregnant. Her diagnosis is a rare, mysterious condition called pseudocyesis. Betrayed by her mind and body and her marriage strained, Amanda turns to neuroscientist Patrick Davis for answers. Patrick understands the strange twists and turns of the human mind better than anyone. But as he spirals ever deeper into Amanda's illness, his own homelife crumbles as his wife, Marissa, struggles to cope with her own loss. Marissa's unique and, some may think, macabre work is her salvation, but it's pulling her further and further away from Patrick. As the two couples confront the fraught intersection of science, death, and human emotion, they venture into the darkest corners of each other's lives. What they find there could change them forever"--Book jacket flap.